Perceived lack of behavioral control is a barrier to a healthy lifestyle in post-menopause: a qualitative study - Khadijeh Khademi; Mohammad Hossein Kaveh; Mahin Nazari; Abdolrahim Asadollahi (BMC, 2024)
Abstract Introduction Menopause is a natural phase in a woman's life, but the quality of life and health of postmenopausal women are often compromised by unhealthy lifestyles. Therefore, it is crucial to identify the factors that influence their well-being. The main objective of this study is to explore the barriers to a healthy lifestyle among Iranian postmenopausal women. Methods Qualitative exploratory research was conducted among postmenopausal women aged 45-65 years in three different health centers located in urban areas with varying economic level in a central city of Iran. These areas represented upscale, downtown, and downscale areas with different economic statuses (wealthy, relatively wealthy, and less wealthy). Nine focus group discussions were held, focusing on managing menopausal symptoms, physical activity, and healthy nutrition. Each topic was discussed separately in a different health center, with 10 women participating in each session. Data analysis was conducted using Graneheim and Lundman's method. Results The study revealed a prominent theme, "perceived lack of behavioral control as a barrier to a healthy lifestyle in post-menopause." Two categories, "False attitudes" and "Perceived inability to engage in behavior," were derived from 26 codes related to managing menopausal symptoms. Furthermore, a category, "Perceived inability to engage in behavior," was formed from 11 to 13 codes related to physical activity and healthy nutrition, respectively. The theme highlighted that the perceived lack of behavioral control prevented the women from adopting a healthy lifestyle. Conclusion Improving perceived behavioral control through the modification of attitudes and abilities is essential for maintaining a healthy postmenopausal lifestyle.